Non-invasive detection of the early phase of kidney injury by photoacoustic/computed tomography imaging. (2nd May 2018) - Pan, Wanma; Peng, Wen; Ning, Fengling; Zhang, Yu; Zhang, Yunfei; Wang, Yinhang; Xie, Weiyi; Zhang, Jing; Xin, Hong; Li, Cong; Zhang, Xuemei
Abstract: The early diagnosis of kidney diseases, which can remarkably impair the quality of life and are costly, has encountered great difficulties. Therefore, the development of methods for early diagnosis has great clinical significance. In this study, we used an emerging technique of photoacoustic (PA) imaging, which has relatively high spatial resolution and good imaging depth. Two kinds of PA gold nanoparticle (GNP)-based bioprobes were developed based on their superior photo detectability, size controllability and biocompatibility. The kidney injury mouse model was developed by unilateral ureteral obstruction for 96 h and the release of obstruction model). Giving 3.5 and 5.5 nm bioprobes by tail vein injection, we found that the 5.5 nm probe could be detected in the bladder in the model group, but not in the control group. These results were confirmed by computed tomography imaging. Furthermore, the model group did not show changes in the blood biochemical indices (BUN and Scr) and histologic examination. The 5.5 nm GNPs were found to be the critical point for early diagnosis of kidney injury. This new method was faster and more sensitive and accurate for the detection of renal injury, compared with conventional methods, and can be used for the development of a PA GNP-based bioprobe for diagnosing renal injury.